1991
DOI: 10.1056/nejm199110103251502
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-up after Partial Removal of a Solitary Kidney

Abstract: Long-term renal function remains stable in most patients with a reduction in renal mass of more than 50 percent. These patients are, however, at increased risk for proteinuria, glomerulopathy, and progressive renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(90 citation statements)
references
References 22 publications
0
87
0
3
Order By: Relevance
“…The tumors were renal cell carcinoma, clear cell type (254), papillary type (62), or chromophobe type (29); oncocytoma (30); urothelial cell carcinoma (33); angiomyolipoma (14); and miscellaneous (27). In toto, 117 (30.7%) had minimal pathologic change as defined by less than 5% GS, less than 10% IF/TA, and mild or no significant vascular sclerosis (interlobular, small arteries, arterioles including hilar arterioles).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumors were renal cell carcinoma, clear cell type (254), papillary type (62), or chromophobe type (29); oncocytoma (30); urothelial cell carcinoma (33); angiomyolipoma (14); and miscellaneous (27). In toto, 117 (30.7%) had minimal pathologic change as defined by less than 5% GS, less than 10% IF/TA, and mild or no significant vascular sclerosis (interlobular, small arteries, arterioles including hilar arterioles).…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] Hyperfiltration effects are further complicated by preexisting vascular, diabetic, or hypertension-associated renal parenchymal changes, which independently contribute to progressive impairment of renal function.…”
Section: Commentmentioning
confidence: 99%
“…[5][6][7] In accordance with this hypothesis, individuals who have undergone nephrectomy have been shown to develop high BP and proteinuria decades after the nephrectomy, 8 -11 as in the case of older recipients with a higher body mass index 12 ; however, renal insufficiency only appears in the case of a 75% reduction in kidney mass and after at least 10 years of follow-up. 9 Kidney transplantation has been proposed as an accelerated model of nephron reduction resulting from the accumulation of several unfavorable factors. For example, repeated injuries, from initial brain death of the donor 13 to ischemia-reperfusion injury, 14 negatively affect the transplant.…”
mentioning
confidence: 99%
“…Furthermore, they show that the occurrence of glomerulosclerosis can be prevented by the use of ACE inhibitors or by a low protein diet (reviewed in 9). In humans, sequential studies of few patients with an important reduction of their renal mass have also shown that a decrease in nephron number can also be responsible for the development of glomerulosclerosis (10,11).…”
Section: Glomerulosclerosismentioning
confidence: 99%